Displasia cemento-óssea florida: relato de caso - Gaetti-Jardim, Éllen Cristina [UNESP]; Santiago Júnior, Joel Ferreira [UNESP]; Guastaldi, Fernando Pozzi Semeghini [UNESP]; Magro Filho, Osvaldo [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Jardim Júnior, Elerson Gaetti [UNESP] (My University, 2010)
The florid cemento-osseous dysplasia is an asymptomatic lesion present in the fibro-osseous maxilla and mandible of uncertain etiology. It has higher expression in females, and patients melanoderm, middle-aged to elderly. This dysplasia is an asymptomatic condition that can be discovered when a radiograph is performed. A biopsy is contraindicated to avoid infection difficult to treat. We report the case of a white woman 52 years old, who searched the Clinic of Surgery and Traumatology Bucco-maxillofacial surgery, Faculty of Dentistry of Araçatuba with pain in the posterior portion of left mandible. After radiographic examination was diagnosed with florid cementoosseous dysplasia. Treatment was instituted clinical and radiographic.

A displasia cemento-ósseo florida é uma lesão assintomática fibro-óssea presente na maxila e mandíbula de etiologia incerta. Possui maior expressão no gênero feminino, pacientes melanoderma e, de meia idade ao idoso. Esta displasia é uma condição assintomática que pode ser descoberta quando uma radiografia é realizada. A biópsia é contra-indicada para evitar infecção de difícil tratamento. Será descrito o caso clínico de uma mulher branca de 52 anos de idade, que procurou a Clínica de Cirurgia e Traumatologia Buco-maxillofacial da Faculdade de Odontologia de Araçatuba com dor na porção posterior esquerda da mandíbula. Após exame radiográfico foi diagnosticada a displasia cemento-óssea florida. Como tratamento, foi instituído o acompanhamento clínico e radiográfico.
Florid cemento-osseous dysplasia: a case report
Keywords: Oral cavit; Mandible; Maxillary neoplasms; Cavidade bucal; Mandíbula; Neoplasias maxilares